2021
DOI: 10.48550/arxiv.2107.08352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can we know about black hole thermodynamics through shadows?

Abstract: We investigate the relationship between shadow radius and microstructure for a general static spherically symmetric black hole and confirm their close connection. In this regard, we take the Reissner-Nordström (AdS) black hole as an example to do the concrete analysis. On the other hand, we study for the Kerr (AdS) black hole the relationship between its shadow and thermodynamics in the aspects of phase transition and microstructure. Our results for the Kerr (AdS) black hole show that the shadow radius r sh , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 177 publications
0
21
0
Order By: Relevance
“…Following Ref. [22][23][24][25], the light ray send from a static observer at position r O transmits into the past with an angle β relative to the radial direction, that is…”
Section: The Shadow Of the Bardeen-ads Bhmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Ref. [22][23][24][25], the light ray send from a static observer at position r O transmits into the past with an angle β relative to the radial direction, that is…”
Section: The Shadow Of the Bardeen-ads Bhmentioning
confidence: 99%
“…By investigating the relations between the shadow and critical behavior of the charged AdS BH, Belhaj et al obtained the critical exponent that perfectly matched the vdW system [23]. Cai et al studied the relationship between shadow radius and microstructure of the charged AdS BH, founding that the shadow can provide the dynamic characteristics of BHs [24]. By constructing the connection between the shadow and Ruppeiner geometry, Wang et al believed the BH shadow can provide information about the small/large phase transition of the charged AdS BH and obtained the normalized curvature scalar at the critical point has a constant value of −3/2 [25].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the investigations on these spacetimes, interplays between the black hole thermodynamics and the optical properties have been established. It has been shown that the shadow size can provide information on the HP phase transitions, the critical behaviors and the microstructure states of the black holes living in AdS geometries [44][45][46]. And the relation between the shadow and the thermodynamics of the black hole has been also developed for regular space-times [47].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we can define a "force" by taking the ratio F 2 := J 2 /S 2 , where J is the angular momentum and S the Bekenstein-Hawking entropy of the black hole. These two thermodynamical variables can be used to define the so-called Ruppeiner geometry [13] -a two-dimensional Riemannian metric in thermodynamic phase space -which has recently gained some attention in the context of black hole microstructure [14][15][16][17][18][19][20][21] and applications to black hole shadows [22][23][24]. Interestingly, the region in the thermodynamic phase space with positive Ruppeiner scalar curvature is marked by the boundary F 2 = 1 As pointed out by Emparan and Myers, at this point the temperature of the black hole starts to behave like a black brane instead of a Kerr-type black hole.…”
Section: Introduction: the Maximum Force Conjecture And Thermodynamicsmentioning
confidence: 99%